Values: intellectuals and policy process in Nigeria: A theoretical cum ideological explanation (2013)
This work studies the intellectuals in Nigeria and their roles in the policy process. After a careful identification of the roles which have been played by Nigeria’s intellectuals since Nigeria’s independence, the paper adopts the belief system framework of public policy analysis together with three ideological categorization of individual personalities. It provides a theoretical cum ideological explanation for the different roles played by these intellectuals in different areas of the political system. These ideological linings of Nigeria’s intellectuals were also seen as contributing both positively and negatively to the actions and inactions of intellectuals in particular and the policy process in general. The paper finally sees the policy process as a rational enterprise which has to be seen as such by intellectuals and the government for meaningful development of Nigeria.